Kisah Luth (Lot) dan Kejahatan Kaum Sodom - Kristianto, Andreas; Listijabudi, Daniel K (Theologia in Loco, 2021)
Abstract The story of Luth (read: Lot) is usually read as a text about homosexuality in both Christianity and Islam. By exploring a cross-textual reading from leading Muslim interpreters in Indonesia, Hamka with Al Azhar Juzu Commentary, Quraish Shihab with Al Misbah Commentary and interpretation of the Ministry of Religion, this article unveils the hidden meaning of Luth’s story, which today’s readers often overlook, especially concerning the text of the Qur'an, namely Surah Asy-Syu’ara 26: 166-175, Surah Al-Naml 27: 54-59 and Surah Al-Ankabut 29: 28-30. Through a cross-textual reading, the article unveils the new meaning of the story, i.e., the crimes of the Sodomites not only related to sexual violence and hostility, but also, with the terms al-fahisyah (abomination), al-sayyiat (crime), al-musrifun (people who are excessive), al-’adun (people who transgress), al-jahl (ignorance), and alkhaba’is (bad deeds), which are the accumulation of various kinds of crimes, crimes, and abominations degrading humanity. The cross-textual reading between the interpreters of the Qur’an and the Bible provides the viewpoints, insights, and values in the cross-textual hermeneutical encounter of different religions, traditions, and scriptures. Keywords: Story of Luth, Christian and Islam, Cross-textual, Homosexuality, Hermeneutic Abstrak Kisah Luth (baca: Lot) biasanya menjadi rujukan untuk berbicara tentang homoseksualitas baik di dalam agama Kristen maupun Islam. Dengan eksplorasi pembacaan secara lintas tekstual dari mufasir Islam terkemuka di Indonesia yaitu Hamka dengan Tafsir Al Azhar Juzu, Quraish Shihab dengan Tafsir Al Misbah, dan Tafsir Kementerian Agama, artikel ini akan menggali makna tersembunyi dari kisah Luth yang sering kali terlewatkan dari perhatian pembaca masa kini, khususnya berkaitan dengan teks Al-Qur’an yaitu Surah Asy-Syu’ara 26: 166-175, Surah Al-Naml 27: 54-59 dan Surah Al-Ankabut 29: 28-30. Makna baru dalam tulisan ini adalah kejahatan kaum Sodom tidak hanya menyangkut soal kekerasan seksual dan ketidakramahan (inhospitality) saja, tetapi juga berkaitan dengan istilah al-fahisyah (kekejian), al-sayyiat (kejahatan), al-musrifun (orang yang berlebihan), al-‘adun (orang yang melampaui batas), al-jahl (kebodohan), dan al-khaba’is (perbuatan buruk), yang merupakan akumulasi dari berbagai macam kejahatan, kriminalitas dan kekejian yang merendahkan martabat kemanusiaan. Dari pembacaan lintas tekstual antara mufasir Al-Qur’an dan Alkitab, kita mendapatkan cara pandang, wawasan, dan nilai-nilai yang membangun dalam perjumpaan cross-textual hermeneutic antara agama, tradisi, dan kitab suci yang berbeda. Kata-kata Kunci: Kisah Luth, Kristen dan Islam, Hermeneutika lintas tekstual, Homoseksualitas, Hermeneutik